Agency, capabilities and rights: a capabilities approach discussion - de Lima, Sérgio Fernando Ferreira; Cochran, Augustus Bonner; Villatore, Marco Antônio César (Direito e Desenvolvimento, 2018)
The aim of this paper is to show how the concepts of agency, capability, and functioning can be aligned in a way that put in evidence the centrality of individual agency. Usually, discussion about the capabilities approach focuses on the limitations and flaws of the theory; here it will be argued that even with limitations and possible problems the capabilities approach could mean a significant paradigm shift for how we think and make Law and public policies. The method used will to analyze some of the principal texts about the subject and to discuss new elements and perspectives that could be brought to bear on the topic. In the end, the article points to a broader way to use the principles and theory of the capabilities approach to describe and analyze legal theory.